Knowledge management adoption to financial institutions using fuzzy AHP and fuzzy TOPSIS techniques. (21st June 2019) - Sani, Saba Alsadat Hosseini; Monfard, Mostafa Vaezi; Sarfi, Elahe
The aim of this study is to identify and prioritise the knowledge management (KM) adoption in financial institutions. Results show that Melal Financial and credit institute, Kosar financial and credit institute and Noor financial and credit institute are on the first, second and last priority, respectively. The results obtained from fuzzy AHP methods indicate that human resources are on the first priority and organisational management, technological factors and cultural factors are on the next priority. Then regarding to the organisational management scales, it is realised that, proper organisational structure to create and share knowledge is most important. Regarding to the technological factors index, it is realised that, technological infrastructure to adopt KM is most important. Regarding to cultural factors index it is realised that, willingness and sharing spirit among members is most important. Regarding to the human resources index, it is realised that, time to share knowledge is most important.